STRATEGI ADAPTASI ORGANISASI DALAM MERESPONS DISRUPSI TEKNOLOGI DAN DAMPAKNYA TERHADAP KINERJA ADAPTIF PEMERINTAH DAERAH - Ade Sudrajat; Ari Safrizal Wildan; Mira Veranita (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Digital technological disruption requires public sector organizations to develop adaptive strategies to sustain performance. This study examines the effect of technological disruption on organizational adaptation strategies and their impact on adaptive performance in public sector organizations in Bandung City, Indonesia, with adaptation strategy as a mediating variable. A mixed methods sequential explanatory design was employed. Quantitative data were collected from a survey of 150 civil servants across public agencies and analyzed using PLS-SEM. Qualitative data were obtained through in-depth interviews with 12–15 key informants to contextualize the quantitative results. The findings show that technological disruption drives organizational adaptation strategies, which subsequently enhance adaptive performance, indicating partial mediation. Qualitative evidence highlights the importance of adaptive leadership, organizational flexibility, digital competencies, and a learning-oriented culture. This study contributes theoretically by integrating contingency theory and dynamic capabilities in a local government context and methodologically by demonstrating the value of a mixed methods approach combining PLS-SEM and qualitative inquiry to explain public sector organizational adaptation mechanisms. This study advances public sector digital transformation literature by empirically demonstrating how organizational adaptation operates as a mediating mechanism rather than a direct outcome of technological disruption.